Assessment of Regulation Compliance and Quality of Sachet Water Factories in Ibadan North Local Government, Oyo State, Nigeria - Durowoju, O. R.; Desogan, A.; Mustapha, M.; Waziri, S. A.; Ibrahim, U. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Provision of clean drinking water is one of the basic human necessities for healthy livelihood. In Nigeria, many people relied on sachet waters as an alternative source of clean drinking water. However, complaints abound regarding lack of proper water quality standard being used which is a major health concern. This study assessed the regulatory compliance of some sachet water production companies and water quality standard in Ibadan North Local Government Area, Oyo State, Nigeria. Questionnaires were administered on factory’s organisational structure and staffing; facilities and equipment; water treatment processes and sanitation practices, Also, Sachet water samples were analysed for the contaminants of Turbidity, Colour, Odour, pH, Nitrate, Chloride, Iron, Electrical conductivity and E-coli count. From the questionnaire analysis, the adherence level with the regulations was poor as majority (60%) of the sachet water factories have poor organisational structure and only 33% have adequate facilities and equipment. However, water quality analysis showed that most of the sachet water parameters tested were within the standard range except for pH values and E Coli count which majority (70%) falls below standard for both. The study concludes that most sachet water brands produced are unsafe for human consumption. There is need for proper monitoring by relevant agencies towards ensuring sachet water factories continuously complied with standard operations for better public health in the study area.